NDUFB6 Polymorphism Is Associated With Physical Activity-Mediated Metabolic Changes in Type 2 Diabetes - Pesta, Dominik; Jelenik, Tomas; Zaharia, Oana-Patricia; Bobrov, Pavel; Görgens, Sven; Bódis, Kálmán; Karusheva, Yanislava; Krako Jakovljevic, Nina; Lalic, Nebojsa M.; Markgraf, Daniel F.; Burkart, Volker; Müssig, Karsten; et al. (Frontiers in Endocrinology, 2021)
The rs540467 SNP in the NDUFB6 gene, encoding a mitochondrial complex I subunit, has been shown to modulate adaptation in exercise intervention studies. Interaction effects with diabetes mellitus remain unclear. Here, we assessed associations of habitual physical activity (PA) levels with metabolic variables and whether the rs540467 SNP exerts a modifying effect. Volunteers with type 2 (n=242), type 1 diabetes (n=250) or normal glucose tolerance (control; n=139) were examined at diagnosis and subgroups with type 1 (n=96) and type 2 diabetes (n=95) after 5 years. Insulin sensitivity was measured by hyperinsulinemic-euglycemic clamps, VO2max by spiroergometry and PA via questionnaire. Translational studies examined insulin signaling and mitochondrial function in Ndufb6 siRNA-treated C2C12 myotubes, with electronic pulse stimulation (EPS) to simulate exercising. PA levels were 6 and 10% and VO2max was 29% and 3% lower in individuals with type 2 and type 1 diabetes compared to controls. Within 5 years, 36% of people with type 2 diabetes did not improve their insulin sensitivity despite increasing PA levels. The NDUFB6 rs540467 SNP modifies PA-mediated changes to insulin sensitivity, body composition and liver fat estimates in persons with type 2 diabetes. Silencing Ndufb6 in myotubes reduced mitochondrial respiration, increased reactive oxygen species and prevented rescue from palmitate-induced insulin resistance after EPS. A substantial proportion of humans with type 2 diabetes fail to respond to rising PA with increasing insulin sensitivity. This may at least partly relate to a polymorphism of the NDUFB6 gene, which may contribute to modulating mitochondrial metabolism and oxidative stress.